Informationsmotorvejen og andre metaforer i computerfagsprog - Grevy, Carlo (HERMES - Journal of Language and Communication in Business, 1999)
In this article I will discuss some of the results of the empirical results of my Ph.D.-project on metaphors in the specialiced languages, especially computer language. In the empirical work I have approximately collected 3000 metaphors in 5 numbers of PC Magazine Denmark, 1997-1998. Approximately 500 of these are highway metaphors. I will start with my critic of Lakoff & Johnson’s empirical basic, whom I assume talk about idealized metaphors and not real metaphors. I will argue, that we have to concern about how metaphors are used in restricted areas, if we want to say something essential about how metaphors really work. I also will introduce the term integrated metaphors, which is essential to understand how metaphors work: they don’t work isolated from each other, on the contrary: they work because they are integrated with other metaphors in the same semantic field. I will close this issue with a concrete discussion of the status of Lakoff & Johnson’s metaphors, where I will focus on Lakoff’s issue on the meta-phors used in the war in the Gulf.